Towards understanding the de-adoption of low-value clinical practices: a scoping review. Issue 1 (December 2015) - Niven, Daniel; Mrklas, Kelly; Holodinsky, Jessalyn; Straus, Sharon; Hemmelgarn, Brenda; Jeffs, Lianne; Stelfox, Henry
Abstract Background Low-value clinical practices are common in healthcare, yet the optimal approach to de-adopting these practices is unknown. The objective of this study was to systematically review the literature on de-adoption, document current terminology and frameworks, map the literature to a proposed framework, identify gaps in our understanding of de-adoption, and identify opportunities for additional research. Methods MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Reviews, the Cochrane Database of Abstracts and Reviews of Effects, and CINAHL Plus were searched from 1 January 1990 to 5 March 2014. Additional citations were identified from bibliographies of included citations, relevant websites, the PubMed 'related articles' function, and contacting experts in implementation science. English-language citations that referred to de-adoption of clinical practices in adults with medical, surgical, or psychiatric illnesses were included. Citation selection and data extraction were performed independently and in duplicate. Results From 26, 608 citations, 109 were included in the final review. Most citations (65 %) were original research with the majority (59 %) published since 2010. There were 43 unique terms referring to the process of de-adoption—the most frequently cited was "disinvest" (39 % of citations). The focus of most citations was evaluating the outcomes of de-adoption (50 %), followed by identifying low-value practices (47 %), and/or facilitating de-adoption (40 %). The prevalence of low-value practices ranged from 16 % to 46 %, with two studies each identifying more than 100 low-value practices. Most articles cited randomized clinical trials (41 %) that demonstrate harm (73 %) and/or lack of efficacy (63 %) as the reason to de-adopt an existing clinical practice. Eleven citations described 13 frameworks to guide the de-adoption process, from which we developed a model for facilitating de-adoption. Active change interventions were associated with the greatest likelihood of de-adoption. Conclusions This review identified a large body of literature that describes current approaches and challenges to de-adoption of low-value clinical practices. Additional research is needed to determine an ideal strategy for identifying low-value practices, and facilitating and sustaining de-adoption. In the meantime, this study proposes a model that providers and decision-makers can use to guide efforts to de-adopt ineffective and harmful practices.